Atomic Arrangement in Metal‐Doped NiS2 Boosts the Hydrogen Evolution Reaction in Alkaline Media. Issue 51 (4th November 2019) - Yin, Jie; Jin, Jing; Zhang, Hong; Lu, Min; Peng, Yong; Huang, Bolong; Xi, Pinxian; Yan, Chun‐Hua
Abstract: We report a novel modulation strategy by introducing transition metals into NiS2 nanosheets (NSs) to flexibly optimize the electronic configurations and atomic arrangement. The Co‐NiS2 NSs exhibit excellent hydrogen evolution reaction (HER) performance with an overpotential of 80 mV at j =10 mA cm −2 and long‐term stability of 90 h in alkaline media. The turnover frequencies (TOFs) of 0.55 and 4.1 s −1 at an overpotential of 100 and 200 mV also confirm their remarkable performance. DFT calculations reveal that the surface dopants abnormally sensitize surface Ni‐3d bands in the long‐range order towards higher electron‐transfer activity, acting as the electron‐depletion center. Meanwhile, the high lying surface S‐sites possess substantially high selectivity for splitting the adsorbing H2 O that guarantee the high HER performance within alkaline conditions. This work opens opportunities for enhancing water splitting by atomic‐arrangement‐assisted electronic modulation via a facile doping strategy. Abstract : Co doped : Cobalt‐doped NiS2 nanosheets (NSs) with optimal eg 1 electron configurations and enhanced Ni 3+ content exhibit excellent activity and stability for the hydrogen evolution reaction (HER) in alkaline media. DFT results reveal that a Co‐NiS2 NSs surface abnormally sensitizes Ni‐3d bands towards higher electron‐transfer.